La gare monumentale de Canfranc à l’épreuve des temps. Grandeur et décadence d’un patrimoine ferroviaire de la montagne aragonaise (Espagne) - Pascal Desmichel (Unité Mixte de Recherche 8504 Géographie-cités, 2008)
The railway station of Canfranc, located on the line of the western transpyrénéen (opened in 1928) did not receive as much traffic as expected during construction. Symbol of a whole country liking to show its dynamism and its modernity by opening with Europe, this vast international station was the object of a considerable architectural and urbanistic plan not to say immoderate with regard to actual railroad traffic (removed on the French side since 1970). Lost in a landscape of high mountain, the second biggest railway station of Europe represents a special heritage for numerous reasons, particularly because the rail landscape seen by the visitor is absolutely unique. Spanish actors are now focusing on renovating of emblematic passengers building today. The rest of the property falls victim to abandonment a little more every day and should be transformed into urban space (according to the plan of discreet architect). This choice of a programmed dismemberment of the railway and a largely non-railway reassignment certainly responds to the desire to enhance this site but destroys what could constitute the largest conservatory in the history of Western railway.